INSIDENSI KHOLANGITIS KRONIK SEBAGAI MANIFESTASI EKSTRAINTESTINAL PENDERITA IBD DI RSPAD GATOT SOEBROTO JAKARTA PUSAT - ARL, Syafruddin; Martamala, Ruswhandi (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2017)
IBD (Inflammatory Bowel Disease) as a disease of inflammation of chronic intestinal. The extraintestinal manifestation is predominantly in the form Pericholangitis, chronic cholitis or primary sclerosing cholangitis (PSC), which usually appear after a few years later from the pop-up cases of IBD with the incidence rate of 5%. Want to know the incidence rate of IBD and PSC in patients were undergoing colonoscopy at RSPAD GS since of March 1, 2016 until February 28, 2017. All patients were undergoing colonoscopy for one year included as a subject of research. Subjects sorted and selected on the findings of the colonoscopy as IBD and non-IBD. Data Cholitis chronic (KHK) is based on the findings of aspartate aminotransferase (AST) and total bilirubin elevated serum and serum albumin divided into groups of KHK-IBD or PSC, KHK-non-IBD, Non-KHK-IBD and Non- KHK-non-IBD. Correlation between the PSC and the PSC with IBD were tested statistically by Fisher, materials taken retrospective descriptive. Data PSC and IBD patients as follows: The incidence rate of IBD and PSC are 18.6% and 5.4%; Correlation PSC with extraintestinal manifestation of IBD acceptable expectation (p = 0.000); demographic data of IBD (30 patients) with male 62.4% (18 people), mean age was 50.6 years and incidence between 40 - 59 years old.